Maximizing Gains from Postal Service Market Liberalization - Sven Heitzler (Weekly Report, 2009)
The upcoming full liberalization of postal service markets under the European regulatory framework offers the chance to further increase regulatory efficiency. Obstacles to competition and barriers to market entry should be systematically removed, and existing obligations for all companies reduced as much as possible. In this connection, universal service obligations should be modernized and flexibly designed. Competitively neutral financing for universal service burdens should also be put in place. Moreover, national or company-specific protectionism should be avoided to boost fair competition and the long-term development of the market.
Keywords: L51; L13; D43; 330; Postal market liberalization; Postal regulation; Barriers to competition; Level playing field